Features and themes of poetry in KOPI (komunitas puisi Indonesia) facebook group - Sugeng Santoso; I Wayan Artika; Ni Made Sania Indri Wahyuni (Universitas Muhammadiyah Malang, 2021)
Going along with the development of technology, literary disciplines also have been developing. Cyber literature becomes popular in this digitalization era which explores the existence of the internet as the medium. One of the large cyber literary communities on Facebook is KOPI (Komunitas Puisi Indonesia) with 64 thousand members. Due to the insufficient research analyzing poetry in the Facebook group, this research analyzed the features of poetry and the themes of poetry in KOPI (Komunitas Puisi Indonesia). Descriptive and qualitative approaches were used in this research. Observation and documentation were used as the techniques in data collecting. The observation was done by reviewing the group’s situation and the documentation is done by reviewing the poetry collections that had been uploaded in this research from the beginning until the middle of February 2021. The data analysis techniques used Miles and Huberman techniques which include: (1) data reduction, (2) data serving, and (3) conclusion/verification withdrawal. The results of this research showed that the dominant poetry features were image illustration and the themes that were used by KOPI group members in writing poetry included the physical themes, moral themes, social themes, egoic themes, divine themes. Physical theme with the most widely used type of love. It can be concluded that the physical theme with the type of “love” is the choice of the theme that the author most favors.